The Anisotropy Induced by a Magnetostriction in Exchange-Biased Two-Layer Films - Gomonay, O.V.; Lukyanchuk, I. (Металлофизика и новейшие технологии, 2014)
The exchange bias at ferromagnetic (FM)/antiferromagnetic (AF) interfaces strongly depends upon the state of antiferromagnetic layer, which is sensitive to mechanical stresses due to its strong magnetoelastic coupling. In a given paper, we consider magnetoelastic effects, which arise at FM/AF interface due to misfit of lattices and magnetic ordering. We show how magnetostriction affects mutual orientation of the AF and FM vectors as well as magnetic easy-axis direction in thin AF layer. The results obtained can be used for tailoring of exchange-biased systems.